Artificial Intelligence-Based Content Generator Technology for Young English-as-a-Foreign-Language Learners' Reading Enjoyment. - Lee, Jang Ho; Shin, Dongkwang; Noh, Wonjun (RELC Journal, 2023)
Artificial intelligence has recently seen tremendous growth, and been applied to several fields, including the second-language domain. In this article, we share an innovative practice based on one of potential artificial intelligence technologies for second-language teaching and learning – artificial intelligence-based content generator, which generates texts based on user's keywords. In total, 121 young English-as-a-foreign-language learners participated in the study, with half of them having engaged in the artificial intelligence-based content generator-based activity, and the other half having received traditional English-as-a-foreign-language reading instruction. We examined the extent to which the artificial intelligence-based content generator-based activity could influence the participants' foreign language enjoyment and interests in reading English books, and the participants were given the survey addressing these variables, prior to and after the innovative practice. It was found that the condition based on the artificial intelligence-based content generator-based activity was more effective in terms of enhancing the target variables, and that the group which engaged in the artificial intelligence-based content generator-based activity was largely in favor of artificial intelligence-based content generator technology. Pedagogical implications for employing this technology in second-language contexts are provided.